Self/Power/Other : Political Theory and Dialogical Ethics - Coles, Romand (Cornell University Press, 1992)
Romand Coles here explores the writings of Augustine, Foucault, and Merleau-Ponty in order to fashion an ethos that emphasizes the value of dialogical relationships between the self and others. In his view, each of these thinkers has made significant contributions that must figure in any reconsideration of the relationship between the self, ethics, and power. Whereas Augustine saw depth as the dimension of freedom and truth, according to Coles's reading, Foucault regarded depth as "that dimension in which we rout out the other and constitute ourselves in light of hegemonic norms implanted deep within us." After drawing out those aspects of Foucault's thought which point toward a "dialogical artistic ethics," Coles explores Merleau-Ponty's philosophy of depth, arguing that it elucidates the "intercorporeality" of the world in a way that emphasizes the value of our dialogical relations with different others. In conclusion, he brings the three thinkers together to assess their rhetorical and philosophical similarities and differences, and to argue against the tendency to see all post-modern thought as nihilistic and incapable of developing an ethico-political stance. Coles's highly original work seeks to provide an alternative to the positions that have structured most recent debate in political philosophy. Thus, his book points up difficulties in both the individualist and the communitarian readings of politics and ethics, even as it seriously explores the ethical dimensions and possibilities of post-modernist thought. His attempt to develop an ethos based on a specific conception of selves and the world enables him to cast provocative light on the continuing dialogue between rationalists and relativists about the nature of both selves and our social and political institutions